Features of organization of backhaul backbone network based on LTE technology - Tokar, L.A.; Tokar, D.I. (Radiotekhnika, 2018)
The questions of organization of backhaul backbone network using LTE technology are considered. The model of a backhaul network using multiprotocol label switching technology is proposed to form the transport basis for existing networks. The transport performance of the network was estimated.